2016
DOI: 10.1016/j.jclepro.2015.12.078
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Product Declarations: exploring their evolution and the factors affecting their demand in Europe

Abstract: This paper presents the findings of an exploratory study conducted to analyse the growing use of Environmental Declarations as environmental communication tools, together with the factors that have led to this situation in Europe. To do so, and focusing on the EPD programme called the International EPD System, an exhaustive analysis was performed of the evolution of Product Category Rules (PCR) and Environmental Product Declarations (EPD). The next step was to draw up a survey to be administered to companies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
(11 reference statements)
0
38
2
4
Order By: Relevance
“…EPDs have recently been promoted in the building sector by the EU regulation No. 305/2011(EC, 2011Ibanez-Fores et al, 2016), and this sector has shown a net increase of issued EPDs (Ibanez-Fores et al, 2016). This is reflected to some extent in the current study because the construction and materials sector presents an LCA presence of approximately 7% in CS reporting for the past 5 years, hence slightly higher than the average (see Table S3 in Results S1).…”
Section: Analysis Of Trendsmentioning
confidence: 52%
See 2 more Smart Citations
“…EPDs have recently been promoted in the building sector by the EU regulation No. 305/2011(EC, 2011Ibanez-Fores et al, 2016), and this sector has shown a net increase of issued EPDs (Ibanez-Fores et al, 2016). This is reflected to some extent in the current study because the construction and materials sector presents an LCA presence of approximately 7% in CS reporting for the past 5 years, hence slightly higher than the average (see Table S3 in Results S1).…”
Section: Analysis Of Trendsmentioning
confidence: 52%
“…Launched in 2002, the United Nations Environment Programme (UNEP)/SETAC Life Cycle Initiative has been working towards building an expert community of practitioners and reaching the worldwide dissemination of the LCA methodology and life cycle thinking among businesses, governments, and consumers through its different working groups (Bjørn, Owsianiak, Molin, & Hauschild, 2018;Sonnemann et al, 2018;Töpfer, 2002 (EC, 2003), the directive on the eco-design of energy using products in the EU region (EC, 2009), the eco-labeling scheme (EC, 2010), the EU better regulation toolbox (EC, 2015), and the PEF and OEF guidance documents (EC, 2016(EC, , 2018a. Type III environmental information on products, in the form of Environmental Product Declarations (EPD; Ibanez-Fores, Pacheco-Blanco, Capuz-Rizo, & Bovea, 2016), are directly associated with conducting an LCA following a set of product categories rules. Type I eco-labeling of products does not require the conduction of LCAs; yet a type I eco-labeled product must fulfill a number of requirements along its life cycle.…”
Section: Lca In Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only around 650 EPDs are currently included in the online database, despite belonging to a wide range of product categories. Besides, Ibáñez-Forés et al [76] explain that EPD are still generally unknown, and that is the reason why few EPD are used, and even fewer are added to the database. Consequently, EPD cannot cover the research demand for many disciplines.…”
Section: Use and Develop Open Access Databasesmentioning
confidence: 99%
“…Today there is an increasing interest across Europe in establishing guidelines that facilitate and drive the measurement and communication of the environmental behavior of products and organizations [15]. Ecolabels are used by manufactures and distributors to provide information about the environmental performance of their good on a voluntary basis.…”
Section: Additional Informationmentioning
confidence: 99%